Structural Relationship of Technology Adoption and Performance Factors in UAE Manufacturing Industry - Saqer Saif Almehairbi , Khalfan Mohamed; Jano, Zanariah; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
The world is rapidly changing as a result of technology, which has played an important role in organisational development by improving operations and reducing obstacles. Businesses are constantly investing in technology in order to improve their performance and gain a competitive advantage over their competitors. Technological advancements assist businesses in automating their systems and management, providing them with the impetus to efficiently target customers through low-cost business solutions. As a result, this paper examined the relationship between technology adoption and the performance of business organisations involved in manufacturing. This study was conducted quantitatively, with data collected via questionnaire survey. The collected data was used to develop the model of structural relationship between the factors using PLS-SEM approach. Based on the validated PLS-SEM model, it was found that performance expectancy, effort expectancy, social influence, and facilitating condition all have a positive relationship with technology adoption. One of the most significant benefits of increased technological use in manufacturing firms is increased revenue through improved performance. The evaluation of the mediation effects of firm size and training on the relationship between technology adoption and manufacturing firm performance in the UAE revealed that the hypotheses' outcomes were positive, indicating that firm size and training do play a role in manufacturing performance. When using technology in manufacturing, the training and firm size have a significant impact on manufacturing performance.